DOES GOVERNANCE MATTER? THE CONDITIONAL IMPACT OF FISCAL DECENTRALIZATION ON PUBLIC WELFARE - Dwipatna, I Made Jyotisa Adi; Andriani, Shadry; Regina (Buletin Studi Ekonomi, 2026)
Fiscal decentralization has been widely implemented in Indonesia with the objective of improving public welfare through greater local autonomy and more responsive public service delivery. Empirical results remain inconsistent, implying that the welfare implications of fiscal decentralization depend on complementary institutional arrangements. This study aims to examine the effect of fiscal decentralization and governance quality on public welfare in Indonesia, as well as to assess whether governance quality moderates the relationship between fiscal decentralization and public welfare outcomes. The study employs a quantitative approach using static panel data covering 29 provinces over the period 2015–2024. A fixed effects model is applied following a series of model selection tests, and mean-centering is used to address multicollinearity arising from interaction terms. The findings from FEM mean-centering (FEM_c) estimation indicate that fiscal decentralization and governance quality each exert a positive influence on public welfare, while the interaction results suggest that better governance strengthens the welfare-enhancing effect of fiscal decentralization. These results highlight that the benefits of fiscal decentralization are conditional upon institutional quality rather than automatic. The study contributes to the literature by integrating governance quality as a critical moderating factor, expanding existing theoretical frameworks on fiscal decentralization. It underscores that enhancing governance capacity at the local level is essential for ensuring that fiscal decentralization effectively improves public welfare in Indonesia.